PERSEBARAN PRODUKSI KOMODITAS TANAMAN HORTIKULTURA, PADI DAN PALAWIJA DI DESA SAWAHAN KECAMATAN NGEMPLAK BOYOLALI - Adhistie Fadila Setyaputri; Danila Desti Ramadhani; Ilhamul Zain Satria Negara; Ulfi Hanum; Wahyu Kisworo (Yayasan Nusantara Hasana Berdikari, 2023)
Sawahan Village is one of the villages in Ngemplak District, Boyolali Regency, Central Java Province. Sawahan Village has an area of 265.8000 Km², of which 78.9708 Km2 of paddy fields are used and 186.8292 Km2 of dry land. Sawahan Village is famous for its many areas used for rice fields, but because it is directly adjacent to the City of Solo, Sawahan Village, which is currently an agglomeration area, experiences many problems, one of which is land conversion. The food crop sector as well as horticulture is a producer of staple foods which are key in maintaining national food security. To support the increase in agricultural and horticultural production, it is necessary to identify land to find out the types of plants that are superior in the land so that land use optimization can be carried out for these types of plants. Until now there has been no information related to the spread of agricultural and plantation food crop commodities in Sawahan Village.